The role of self-esteem as mediators between parent-child attachment and attitude towards sexual behaviour among adolescents pregnant out of wedlock - Shahruddin, Nor Jum'awaton; Mansor, Mariani; Madon, Zainal; Hamsan, Hanina Halimatusaadiah (Penerbit UTM Press, 2018)
This study examined the mediating influence of self-esteem on the relationship between parent-child attachment and sexual attitude behavior among adolescent out of wedlock pregnancy in Peninsular Malaysia. Based on cross-sectional design, the sample of this study consisted of 130 teenagers pregnant out of wedlock aged between 14 years and 19years from 4 welfare institutions in the states of Selangor, Perak, Johor and Kelantan participated in this research. Findings revealed that the level of parent-child attachmen is moderate, a hight of self esteem and respondents indicated a high level ofattitude sexual behavior. Results of Pearson’s correlation analysis revealed that there were significant relationships between parent-child attachment with attitudes toward sexualbehaviour(r = -.220, p <.05) and a significant correlation between self esteem and attitude sexual behavior (r = .708, p <.05). In conclusion, the parent-child attachment and self esteem related to attitude sexual behavior. The findings of this study prove that parents should maximize time to ensure that youth do not feel isolated in the family. At the same time, this study also suggests several alternatives in order to curb sexual misconduct among the teenagers today.